Pengaruh Faktor Ekonomi Terhadap Angka Putus Sekolah di Kecamatan Sumbang - Nadya Cindy Aurellia; Eka Fajariani Adika Putri; Dijan Rahajuni; Oki Anggraeni (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research aims to examine the influence of economic factors on the dropout rate in Sumbang District, Banyumas Regency. Quantitative methods are used by collecting data through questionnaires and secondary data sources, then analyzed using multiple linear regression. The main variables studied are unemployment and poverty as economic factors that affect education. The results of the analysis show that both variables have a significant influence on the level of education with a contribution of 23.8% to the variation in dropouts. In addition to economic factors, there are also other factors that play an important role such as student motivation, family support, social environment, and health conditions. This study concludes that handling the problem of dropping out of school must be carried out with a comprehensive approach that does not only focus on financial assistance, but also on improving the quality of education and a conducive learning environment